Three dimension high definition manometry evaluated postoperative anal canal functions in children with congenital anorectal malformations - Zhao, Jiawei; Zhang, Yanan; Xiong, Yu; Du, Jingbin; Chen, Yongwei; Guo, Weihong; Huang, Jinshi (Frontiers in Pediatrics, 2023)
Background We aimed to evaluate the function of the reconstructed anal canal in postoperative anorectal malformations (ARMs) patients through three dimension (3D) high-definition anorectal manometry. Methods From January 2015 to December 2019, 3D manometry was performed as a postoperative functional assessment of patients with ARMs divided into age subgroups based on the time of manometry. Manometric parameters, such as the length of the anorectal high-pressure zone (HPZ-length), the mean resting and squeeze pressure of HPZ (HPZ-rest and HPZ-sqze), recto-anal inhibitory reflex (RAIR), and strength distribution of the anal canal, were collected and compared with age-matched controls. Their functional outcomes were analyzed with SPSS 23.0 software for statistical analysis. Results 171 manometric measurements were performed on 142 postoperative patients (3 months∼15 years). The HPZ-rest in all patients was significantly lower than in age-matched controls (p < 0.05). HPZ-sqze was notably decreased in patients older than 4 years, whereas other age groups were comparable to controls (p < 0.05). The proportions of asymmetric strength distribution and negative RAIR were higher in ARMs patients. The type of anorectal malformations and lower HPZ-rest were the impact factors affecting postoperative functional outcomes. Conclusions The majority of the ARMs patients had acceptable functional outcomes. 3D manometry can objectively assess the reconstructed anal canal function. The patients with fecal incontinence had a high proportion of extremely low HPZ-rest and HPZ-sqze, negative RAIR, and asymmetric strength distribution. The manometric details will help the clinicians explore the causes of defecation complications and guide further management.